2020
DOI: 10.1007/s11596-020-2225-x
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Tfh Cells and Germinal Center in Deceased COVID-19 Patients

Abstract: The COVID-19 pandemic caused by SARS-CoV2 is characterized by a remarkable variation in clinical severity ranging from a mild illness to a fatal multi-organ disease. Understanding the dysregulated human immune responses in the fatal subjects is critical for management of COVID-19 patients and the pandemic. In this study, we examined the immune cell compositions in the lung tissues and hilar lymph nodes using immunohistochemistry on 6 deceased COVID-19 patients and 4 focal organizing pneumonia (FOP) patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 20 publications
1
52
0
3
Order By: Relevance
“…Deficient ICOS expression and lack of functional ICOS/ICOS-L interactions in humans is associated with common variable immunodeficiency (CVID), which manifests as a decreased in memory class-switched B cells and poor germinal center formation 26, 27 . Defective ICOS-L mediated co-stimulation may be a causal factor in inducing germinal center defects that have been recently reported in severe CoViD-19 15, 16 .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Deficient ICOS expression and lack of functional ICOS/ICOS-L interactions in humans is associated with common variable immunodeficiency (CVID), which manifests as a decreased in memory class-switched B cells and poor germinal center formation 26, 27 . Defective ICOS-L mediated co-stimulation may be a causal factor in inducing germinal center defects that have been recently reported in severe CoViD-19 15, 16 .…”
Section: Resultsmentioning
confidence: 81%
“…This delayed B cell response and the subsequent loss of humoral immunity despite a protracted course of disease in CoViD-19 subjects raises concerns over the natural robustness of long-term immunity to SARS-CoV-2 that may mirror waning immunity observed with SARS-CoV-1 30, 31 . Pathological studies in a cohort of deceased CoViD-19 subjects demonstrated a lack of T and B cell responses in lung tissue and a stark ablation of germinal centers within draining hilar lymph nodes 15 . A separate study on lymph node and spleen biopsies demonstrated a similar pattern in live CoViD-19 subjects 16 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Convalescent patients contain SARS-CoV-2 reactive CD4 T cells (up to 100% of patients) and CD8 T cells (∼70% of patients), including CD4 T FH cells capable of providing help to B cells (29)(30)(31)(32). Consistent with a role for T cells in helping B cells in COVID-19, virus-specific T and T FH cell numbers correlated with nAB and AB titers and deceased COVID-19 patients lacked T FH cells and germinal centers in their draining hilar lymph nodes correlated with reduced AB levels (32)(33)(34)(35)(36)(37). T cell reactivities in recovered patients covered multiple SARS-CoV-2 proteins and particularly targeted immunodominant epitopes in the spike (S), membrane (M), and nucleoproteins (N), indicating a benefit for including these proteins in vaccine designs rather than only S as done in several current vaccines (32,38).…”
Section: The Case For T Cellsmentioning
confidence: 82%
“…exalted tfh cells in circulation have tracked concurrently with decreasing viral load in non-severe cases (thevarajan et al, 2020). nonetheless, tfh cells deficiency could be seen in secondary lymphoid organs of decedent CoViD-19 cases suggesting kinked antibody maturation may be instrumental in death (Duan et al, 2020). Adult rhesus macaques after being infected with sARs-CoV-2 corroborated assemblage of proliferating, and activated tfh cells in peripheral blood.…”
Section: T Lymphocytes and Sars-cov-2 Interactionmentioning
confidence: 87%